Assessment of SIWES Relevance to Business Education Programme Objectives - Ibrahim Yinka Agbeyinka (Indonesian Academy of Social and Religious Research (IASRR), 2025)
SIWES, was created to determine how much theoretical knowledge students in engineering technology and other related fields in Nigerian institutions offering technology-based courses had in relation to the type of work experience that employers expected of them. Business education aims to support the development of the business skills required to operate successfully in the workplace, whether an employer or an employee. This study aimed at examining assessment of SIWES relevance to business education programme objectives. The participants in this study were residents of Abuja metropolis, FCT, Nigeria. The sample size was calculated using the population figure, from which a total of 145 responders were chosen. The research selected for this study was survey research design and Taro Yamane's formula was utilized. The results based on respondents' responses show a relationship between SIWES and business education programme objectives. Additionally, 8 of the respondents strongly disagreed that there is a relationship between SIWES and business education programme objectives. The study recommends that experienced staff members keep a close eye on and oversee the learning progress of business education students.